PENGARUH PENGGUNAAN METODE LATTICE MULTIPLICATION TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IV SD INPRES BONTOMANAI - Fajria Salsabila; Nasrah; Andi Mulawakkan Firdaus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study showed that the average pretest score of 33.33 was in the low category, while the average posttest score of 75.00 was in the high category. The results of the normality test showed that the data were normally distributed and the homogeneity test showed that the data variance was homogeneous. Based on the results of the hypothesis test, a significance value (Sig 2-tailed) <0.05 was obtained, so the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. This shows that there is a significant influence of the use of the Lattice Multiplication method on improving students' mathematics learning outcomes. Thus, the Lattice Multiplication method has been proven effective in improving students' mathematics learning outcomes, both in the cognitive, affective, and psychomotor aspects, especially in the material of multiplication arithmetic operations.